KARTU TANDA PENDUDUK TANPA KOLOM AGAMA DALAM PERSPEKTIF EKSISTENSIALISME SARTRE - Surya Desismansyah Eka Putra (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2016)
The concept of freedom is a form of analysis on how the free word was present and exist as a tangible manifestation of the contemporary world in the face of uncertainty. Humans really want to look for its existence as a creature. Existentialism tried to leave the path of light that human nature is the existence in the world. Is a self-proclaimed Sartre the existentialist philosophy of abiding by its main slogan, "Man is condemned to be free", and therefore "existence precedes essence". Discussion of existentialism is related to the phenomenon of the elimination of religion column in the National Identity Card in Jakarta. Policy toward the National Identity Card would try to analyze the concept of freedom of Sartre's existentialism using conflict as an epistemological approach Sartre's existentialism. In keeping with the theme, this article seeks to uncover the link between the elimination of religion column with Sartre's existentialism models. Because basically atheistic existentialism concept and not so see the side of spiritualism as the main thing